SISTEM PENDUKUNG KEPUTUSAN PENILAIAN KINERJA GURU MENGGUNAKAN METODE MULTI ATTRIBUTE UTILITY THEORY (MAUT) DI SMA NEGERI 10 KOTA TERNATE - Abriyanto A. Gani; Santosa Santosa; Mustamin Hamid (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2022)
Implementing a quality education process is a must for every school, as is the case with SMA Negeri 10 Ternate City. SMA Negeri 10 Ternate City always encourages the improvement of teacher professionalism by monitoring the work of teachers in implementing their duties so that the predetermined competency standards can be achieved. SMA Negeri 10 Ternate City is still manual and not so detailed (detailed). With the assessment that is not detailed, it is feared that there will be a subjective assessment (based on personal interests), which can cause social jealousy for teachers who have not received achievements. To overcome these problems, a decision support system was designed using the Multi Attribute Utility Theory Method. As for in this study using 5 criteria. In this study, the application uses the PHP programming language, while the database uses MySQL. The final result of this study found that the decision support system with the MAUT method was able to overcome problems in assessing teacher performance.